The governance of director compensation - Fang, Lily; Huang, Sterling (Journal of Financial Economics, 2024)
The average total compensation of directors in U.S.-listed companies was $342,030 in 2020, 5.06 times the median household income. Directors set their own pay, giving rise to potential self-dealing. We argue and document that in the presence of self-dealing, external mechanisms such as legal standards act as effective means of governance. Following a landmark Delaware court ruling that subjected director pay to a more stringent legal standard, Delaware-incorporated firms reduced director compensation relative to non-Delaware firms and experienced positive and non-transient stock price reactions. Our results indicate that proper governance of director compensation enhances firm value.